2019
DOI: 10.1186/s13033-019-0283-x
|View full text |Cite
|
Sign up to set email alerts
|

Primary health care nurses attitude towards people with severe mental disorders in Addis Ababa, Ethiopia: a cross sectional study

Abstract: Background Negative attitude and discriminatory behavior of health professionals constitute a major obstacle in psychiatric care and have been pointed out as a key issue in working with mental illness. Understanding about the attitude of nurses is crucial for quality and holistic care of psychiatric services and essential for the successful integration of mental health into primary health care. However, there is a paucity of study to examine the attitude of primary health care nurses towards sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 20 publications
2
20
0
1
Order By: Relevance
“…Similarly, a study in Saudi Arabia showed 44.7% of the respondents had an unfavourable attitude towards mental illnesses 39. Studies in Addis Ababa,47 48 China49 and Kuwait50 found most PHC providers still held a pessimistic attitude towards mental illness. This finding is much lower than in the study among health extension professionals in Addis Ababa, Ethiopia, which revealed that 93.4% of health extension professionals had a negative attitude towards mental illness 18.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, a study in Saudi Arabia showed 44.7% of the respondents had an unfavourable attitude towards mental illnesses 39. Studies in Addis Ababa,47 48 China49 and Kuwait50 found most PHC providers still held a pessimistic attitude towards mental illness. This finding is much lower than in the study among health extension professionals in Addis Ababa, Ethiopia, which revealed that 93.4% of health extension professionals had a negative attitude towards mental illness 18.…”
Section: Discussionmentioning
confidence: 97%
“… 21 Finally, as in high-income settings, patients may demand services that conflict with current evidence and providers may also have negative attitudes toward EBP, seeing it as reducing their autonomy and limiting their clinical choices. 34 …”
Section: Introductionmentioning
confidence: 99%
“…Similarly, an earlier study by Egbe et al ( 2014 :5) revealed that advanced mental health nurses verbally abused mental healthcare users in healthcare facilities. A recent African study conducted by Sahile et al ( 2019 :6) revealed that professional nurses, without or with basic psychiatry nursing, displayed more negative attitudes towards mental healthcare compared to psychiatric nurses who had completed advanced training.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Martensson et al ( 2014 :783) concurred that psychiatric nurses, who were frequently in contact with the mental healthcare users, displayed positive attitudes towards them. According to Sahile et al ( 2019 :6), increased personal contact with mental healthcare users reduced psychiatric nurses’ negative attitudes. The study by Basson et al ( 2014 :524) affirmed that advanced psychiatric nurses displayed more positive attitudes than the professional nurses with basic psychiatric nursing training.…”
Section: Discussion Of Findingsmentioning
confidence: 99%